Broadway, looking into Frederick Street Port of Spain - (:unkn) unknown (My University, 2010)
Description on the back of the postcard: "Broadway looking into Frederick Street, Port-of-Spain. Main business section of Trinidad, B.W.I."
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Streets--Trinidad and Tobago; Architecture--Trinidad and Tobago; Stores, Retail--Trinidad and Tobago; Frederick Street (Port of Spain); Broadway (Port of Spain)